A STUDY OF THE REINFORCEMENT USED BY ENGLISH TEACHER IN 6A CLASS AT SD LAB UNDIKSHA SINGARAJA - Pratiwi, M. B. A; Sudirman, Sudirman; Adnyani, L. D. S (International Journal of Language and Literature, 2018)
This study was a descriptive study aimed at describing the components and the implementation of reinforcement used by English teacher in 6A class at SD LAB Undiksha Singaraja. The subjects of this study were an English teacher and 39 students. The data of this study were collected by observation and interview. The result of this study showed that the English teacher in 6A class at SD LAB Undiksha Singaraja used various kinds of reinforcement such as verbal, gestural, contact, and proximity reinforcement. Positive and negative reinforcement were consisted by each of those types. For positive reinforcement, the teacher used “good, very good, well done, good enough, that’s right, nice, smiling, nodding head, thumb up, applause, touching the students, standing next to the students, and sitting close with the students”. For negative reinforcement, the teacher used “sssst, calling students’ name, giving warning, giving explanation, and putting forefinger in front of the lips”. Besides, the teacher used four ways in implementing the reinforcement: given with warmth and enthusiastic, emphasized on meaningfulness, given to both group and individual, and given with various types and purposes. Key words: elementary school, reinforcement